Factors determining institutional delivery in eastern part of India - Madhumita Mukherjee; Manas Pratim Roy (Tzu Chi Medical Journal)
Objective: Institutional delivery (ID) plays a vital role for determining the outcome of pregnancy and ensuring care to mother and newborn. The present study aims to find out the correlates of ID from the eastern part of India. Materials and Methods: Data from National Family Health Survey 4 were analyzed for three states – Bihar, West Bengal, and Jharkhand, keeping district as a unit of analysis. Correlation and regression were used for finding out the determinants of ID. Results: Overall, 67.8% of deliveries were conducted in hospitals. All the three states were able to improve performance on related health parameters like antenatal care. After adjusting for other variables, on multiple linear regression, female literacy was significantly related to ID. Conclusions: Social parameters need to be focused for encouraging ID.